Kebijakan Penanggulangan Prostitusi Online Melalui Media Sosial - Samusamu, Roygers; Pasalbessy, Jhon Dirk; Adam, Sherly (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The existence of a criminal law policy in an effort to combat online prostitution cannot be separated from the existence of cases of online prostitution in Indonesia. Purposes of the Research: The current positive law regulations have not been able to tackle the crime of online prostitution through social media in Indonesia. So it needs to be reviewed in formulating criminal provisions relating to online prostitution to create a better arrangement in the future. Methods of the Research: Type of research: normative juridical, the approach used is the statute approach, the conceptual approach, and the case approach. The sources of legal materials used are Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials. The technique for reviewing and collecting primary, secondary and tertiary legal materials is to use documentation studies. The data analysis used in normative legal research is qualitative analysis Results of the Research: Based on the results of the study, it was found that the concept of online prostitution prevention policies through social media can be overcome with feminist policies so that they can position women according to conditions with criminalization, legalization and decriminalization approaches by eliminating criminal acts of online prostitution through social media based on the socio-cultural background of the Indonesian people and state, while other approaches can also be considered as a policy concept for overcoming the crime of online prostitution through social media. The policy of overcoming the crime of online prostitution through social media has been integrated with criminal law because online prostitution through social media can be handled using criminal law outside the Criminal Code which has a special nature, namely Law Number 21 of 2007 concerning the eradication of criminal acts of trafficking in persons. the shortcomings of the Criminal Code, therefore in an effort to overcome the crime of online prostitution, policies are needed that can provide guarantees and protection to women as perpetrators of online prostitution with various policies and approaches born from socio-cultural values.